EFEKTIVITAS PROGRAM PENANGANAN FAKIR MISKIN DI KABUPATEN KAMPAR STUDI KASUS BANTUAN PENINGKATAN KETERAMPILAN DI KELURAHAN SUNGAI PAGAR - Afrinaldi, M.; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Program of handling poor people in Kampar district case study of skill improvement assistance in fence river village through implementing by poverty eradication coordination team which this program try to eradicate poverty especially in river village of fence, this problem review want to know how the implementation of program handling poor have run Effective or ineffective in accordance with government and community expectations. And what are the factors that influence in the implementation of the poor handling program through skills training in Sungai Pagar Village Kampar Kiri Subdistrict.The theory used by writer in this research is Sutrisno theory (2007: 126-127) which explain about program comprehension, right on target, on time, achieving goal and real change. Researcher use qualitative descriptive method. In the data collecting researchers using observation techniques, interviews and documentation.The results of this study resulted that the implementation of the program handling poor people stminimnya budget cases skill training assistance is not fully optimal and there are still many obstacles that occur, then the factors that affect training activities in the implementation of the program handling poor people through the help of skills training conducted by the team Coordination of regional poverty reduction that is human resources and lack of budget.Keywords: Fakir Poor, Skill Training, Sungai Pagar Village